Conceptual Design of Spacesuit Hard Hip Joint - Wang Zhen-wei; Chen Peng; Lin Dan-lan (International Journal of Aerospace Engineering)
Spacesuit hip joint plays an important role on astronaut activities, such as planetary walking and surveying. This paper proposes a conceptual design of hard hip joint in consideration of the coupling effect of spacesuit hip joint and astronaut thigh. Firstly, lower extremity activities are introduced to illustrate the mobility of hard hip joint, such as walking, kneeing, and abduction. A conceptual design of hard hip joint is explained in detail, including geometric structure, components, design parameters, and mechanism models. Secondly, a 3-linkage coupling mechanism model is built up by synthesizing that conceptual design of hard hip joint. An equiangular dual-perpendicular representation method is brought out to parameterize that mechanism model of hard hip joint. Particularly, four geometric constraints are, respectively, given out to avoid impact between the hip joint and the thigh and to ensure the continuity of thigh motion. Finally, motion equations of hip joint parts are established by using coordinate transformation and vector representation. A case study is conducted to verify the correctness of the proposed representation method and that coupling mechanism model.